The Analysis of Stunting Implementation Policy in Tegal Regency - Rosyida, Melina; Kushandajani, Kushandajani; Herawati , Nunik Retno (Lenggogeni Data Publishing, 2024)
Tegal is a regency with the highest stunting prevalence in toddlers in Central Java with a percentage of 22.3% in 2022. Currently, the regency has become the prioritized locus of stunting intervention in Indonesia. Tegal regency government issued the Regent Rule of Tegal Number 4 in the Year 2023 about the Communication Strategy of Behavioral Changes in Lowering Stunting Prevalence in 2023 - 2026 as the prevention and effort of decreasing the stunting rate. This research revealed the implementation of stunting prevention policy in Tegal by applying the exploratory implementation model of George Edward III, Marilee S. Grindle, and Mazmanian & Sabatier based on the triangular perspective of policy analysis. This descriptive qualitative research describes a variable orally from the respondents and the doers by observing them. The researchers collected the data by interviewing, documenting, and promoting the literature study. The researchers also interviewed the Health Agency of Tegal and Public Health Care of Kedungbanteng district. The results showed that the applied policy met the regulation in terms of local government and local apparatus organization, OPD, with collaboration and effort to realize inter-sectoral cooperation from regency to village levels. The concrete step in preventing stunting includes the provision of nutritionist teams at Kedungbanteg Public Health Care and the establishment of a police center to prevent stunting prevalence. The results were - gaining the top 99 awards of Public Service Innovation in 2023 by the Ministry of State Apparatus Utilization and Bureaucratic Reform. However, the researchers found hindrances in distributing stunting prevention at most pubic health care units in Tegal. They had not applied the concrete steps and had to improve the human resources by joining training for the cadres so they could use the measuring tool of stunting for toddlers.